Implementasi Kewirausahaan Berkelanjutan Pada UMKM Kopi Untuk Pariwisata Di Kabupaten Tapanuli Utara - Pardede, Ester Elisabeth; Dalimunthe, Femmy Indriany (SEIKO : Journal of Management & Business, 2026)
ABSTRACT This study aims to analyze the implementation of sustainable entrepreneurship in Wine Coffee Gogo MSME and its relation to tourism development in North Tapanuli Regency using the Triple Bottom Line framework. A qualitative approach was employed, with data collected through direct observation, in-depth interviews with the business owner, and field documentation. The analysis examined business practices across three sustainability dimensions: economic, social, and environmental. The findings Indicate that the economic dimension is the most dominant, reflected in product innovation based on local coffee resources that generates added value and strengthens the enterprise’s position within the regional value chain. In the social dimension, local workforce empowerment and women’s involvement in business management demonstrate contributions to community-level economic distribution, although formal partnership systems have not yet been established. Meanwhile, the environmental dimension is manifested through the use of locally sourced raw materials and production efficiency; however, environmental management practices remain insufficiently formalized. This study highlights that locally based MSMEs play a strategic role as a linkage between entrepreneurship and sustainable tourism development. The contribution of this research lies in emphasizing the importance of institutional integration and an ecosystem-based approach in strengthening the implementation of sustainable entrepreneurship at the micro-enterprise level. Keywords: Sustainable entrepreneurship; Triple Bottom Line; Coffee MSMEs; Local product innovation; Sustainable tourism Abstract Penelitian ini bertujuan menganalisis implementasi kewirausahaan berkelanjutan pada UMKM Wine Coffee Gogo dalam kaitannya dengan pengembangan pariwisata di Kabupaten Tapanuli Utara menggunakan kerangka Triple Bottom Line. Pendekatan penelitian yang digunakan adalah kualitatif dengan teknik pengumpulan data melalui observasi langsung, wawancara mendalam dengan pemilik usaha, serta dokumentasi lapangan. Analisis dilakukan dengan mengkaji praktik usaha berdasarkan tiga dimensi keberlanjutan, yaitu ekonomi, sosial, dan lingkungan. Hasil penelitian menunjukkan bahwa dimensi ekonomi merupakan aspek yang paling dominan melalui inovasi produk berbasis kopi lokal yang menghasilkan nilai tambah dan memperkuat posisi usaha dalam rantai nilai daerah. Pada dimensi sosial, praktik pemberdayaan tenaga kerja lokal dan keterlibatan perempuan dalam pengelolaan usaha menunjukkan kontribusi terhadap distribusi manfaat ekonomi komunitas, meskipun belum didukung sistem kemitraan yang terstruktur. Sementara itu, dimensi lingkungan tercermin melalui pemanfaatan bahan baku lokal dan efisiensi produksi, namun praktik manajemen lingkungan masih perlu diperkuat secara formal. Penelitian ini menegaskan bahwa UMKM berbasis potensi lokal memiliki peran strategis sebagai penghubung antara kewirausahaan dan pembangunan pariwisata berkelanjutan. Kontribusi penelitian terletak pada penegasan pentingnya integrasi kelembagaan dan pendekatan ekosistem dalam memperkuat implementasi kewirausahaan berkelanjutan pada skala usaha mikro. Kata kunci: Kewirausahaan berkelanjutan; Triple Bottom Line; UMKM Kopi; Inovasi produk lokal; Pariwisata berkelanjutan.